EVALUASI PROGRAM PEMBELAJARAN BINA DIRI ANAK TUNAGRAHITA DI SMALB SANTA LUSIA BEKASI KELAS XII PADA MASA PANDEMI COVID-19 - Sulastri Sulastri; Witarsa Tambunan; Mesta Limbong (Jurnal Manajemen Pendidikan, 2022)
The self-development learning program is implemented to form the independence of children with special needs. The purpose of the study is to determine the needs assessment, to obtain a complete picture of the planning program, to describe the formative evaluation and summative evaluation of the self-development learning program for mentally retarded children at SMALB Santa Lusia Bekasi Class XII during the COVID-19 Pandemic. This study uses an evaluation method with a qualitative approach. The data obtained through observation and interviews were analyzed to evaluate the implementation of the self-development learning program. The research subjects were 7 students and 7 parent informants and 2 class teacher informants. The results of the research on the Need assessment aspect were carried out through the following procedures: 1) Observe all self-development programs. 2) Analysis of children's needs. 3) Determine priority programs. Aspects of the self-development program for mentally retarded children are: initial activities, core activities, and closing activities. Aspects of Formative evaluation, the overall self-development learning program was carried out well. The teacher consistently implements the planned program. However, there are two obstacles; 1) Teachers cannot accompany and guide directly. Even though all subjects still need guidance and direction during self-development learning takes place. 2) The participation of parents in the self-development learning program is still low, as evidenced by the implementation of the program most children are not accompanied by their parents. In the Summative evaluation aspect, the results shown in this evaluation are that the subject still needs guidance and direction in carrying out self-development learning activities, the dependence of mentally retarded students is still quite high. The impact: 1) Subjects are getting to know self-development tools and know how to take care of themselves. 2) Learning that took place during the COVID-19 pandemic indirectly educates students and their families about technological advances and their integration into learning.